From sludge to sustained-release biochar-based phosphorus fertilizer: CaO-mediated phosphorus transformation, soil amelioration, and agronomic performance across contrasting soil types - Zhengkang Zou; Xiaoxiao Xu; Sha Liang; Beibei Dou; Wenbo Yu; Huabo Duan; Jiakuan Yang; Xiong Shi (Biomass and Bioenergy, 2026)

APLN, a novel prognostic biomarker, contributes to esophageal carcinoma development - Weifeng Xu; Caiyun Nie; Chunbaixue Yang; Zhen Liu; Guanghui Liang; Penghui Yu; Huifang Lv; Beibei Chen; Jianzheng Wang; Saiqi Wang; Jing Zhao; Yunduan He; et al. (Functional & Integrative Genomics, 2026)

Parent material modulates land use effects on soil organic carbon fractions but not inorganic carbon in subtropical red soils - Rui Jiang; Shuai Liu; Yu Zhang; Enze Xie; Beibei Fan; Fahui Jiang; Samuel Adingo; Lei Gao; Xinhua Peng (Soil and Tillage Research, 2026)

Efficient removal of norfloxacin in the full spectrum by compounding carbon dots on cobalt atom-anchored nitrogen‑carbon-based photoelectrocatalytic cathode - Beibei Liu; Xiangting Hou; Lumeng Jia; Mengxue Li; Wenchao Yu; Zhaoyong Bian; Hui Wang (Chemical Engineering Journal, 2026)

A facile and scalable strategy to construct superhydrophilic PET membranes for ultrahigh-flux oil–water separation - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2026)

Distinct hydrolyzed Al-Ti species govern the coagulation behavior and subsequent anaerobic fermentation of CEPS sludge - Beibei Liu; Na Pan; Chunyi Sun; Weiying Xu; Wen Song; Liangguo Yan; Tao Yan; Yu Du; Yanxia Zhao; Baoyu Gao (Water Research, 2026)

New insights into the temporal speciation of phosphorus during anaerobic digestion of wetland biomass wastes - Fan Yu; Junxia Wang; Zhi Wang; Lan Mu; Xutong Wang; Qianqian Guo; Xiaoqiang Cui; Yanjun Hu; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Development of the DNDC-SubS 1.0 model for simulating long-term dynamics of crop yield and soil organic carbon under subsoiling - Wenzhou Guo; Jianjun Yang; Shuaibo Shao; Xiao Huang; Yu Yan; Conrad Zorn; Beibei Wang; Jiarui Wu; Shenchao Qiao; Chaoqing Yu; Ligang Wang (Agricultural Systems, 2026)

Decentralized Distributed Vehicle-Road-Cloud Integration Systems: A Paradigm Shift in Smart Urban Mobility and Development - Zhiqin Ma; Nok Ko; Kunlin Yu; Hongjian Lu; Beibei Liu; Qing Zhou; Andong Wang; Zixian Wei; Changyuan Yu (Sustainable Cities and Society, 2026)

Precise engineering of bimetallic sites via molecular coordination strategy for enhanced bifunctional oxygen electrocatalysis - Zhenbei Yang; Zhe Wang; Han Liu; Xiaoyan Jin; Qitong Ye; Zhe Lu; Ruojie Xu; Beibei Yu; Yifan Zhang; Kexin Kong; Yipu Liu; Seong-Ju Hwang; et al. (Science Bulletin, 2026)

Immune dysregulation and cellular dysfunction mediate di-n-pentyl phthalate–induced hepatotoxicity: Insights from single-cell RNA sequencing - Yu Gan; Yongyi Luo; Xiandong Ye; Kaiyan Zhang; Zhenqiu Xia; Lei Yang; Chaoming Zhou; Gan Xie; Wenyan Zhong; Tengfei Yuan; Shuimiao Lin; Yuan Fang; et al. (Food and Chemical Toxicology, 2026)

Soil microbial biogeography: from maps to blueprints - Gui-Feng Gao; Shuo Jiao; Ke Dong; Xu Liu; Xin Xin; Beibei Chen; Kunkun Fan; Yu Shi; Congcong Shen; Teng Yang; Minyu Jing; Siyu Chen; et al. (Soil Ecology Letters, 2026)

Legume identity shapes soil multifunctionality and microbial networks in long-term cereal-based rotations - Shuting Yu; Shuo Li; Jin Yang; Kees Jan van Groenigen; Guiying Jiang; Mengru Wang; Beibei Wang; Fang Liu; Haitao Liu; Xiaolei Jie; Shiliang Liu (Applied Soil Ecology, 2026)

6H2L, a novel derivative of bifendate, dually suppresses glycolysis and glutaminolysis in hepatocellular carcinoma via inhibiting YAP stability - Beibei Zhang; Kaixuan Sheng; Yue Yan; Xinlei Wang; Xinning Cheng; Rong Liao; Zhiyi Yang; Mengyi Li; Fan Wang; Qi Qi; Yu Wang; Chenglin Li (Chemico-Biological Interactions, 2026)

Cephaeline promotes ferroptosis in breast cancer via p53/SLC7A11/GPX4 axis - Xiaohong Li; Jinghan Yu; Beibei Lin; Yudiao Gong (DARU Journal of Pharmaceutical Sciences, 2026)
Background Cephaeline (CPL), a bioactive compound derived from the medicinal plant Ipecacuanha, has demonstrated inhibitory effects on several tumor types. Nevertheless, its role in breast cancer and the underlying molecular mechanisms remain largely unexplored. Objectives This research aimed to investigate the anti-cancer potential of CPL in breast cancer cells. Methods The IC50 of CPL was determined using the CCK-8 assay. Subsequently, the effects of CPL on cell migration and proliferation were assessed through wound healing (scratch) and colony formation assays, respectively. Additionally, MDA and GSH levels were quantified using ELISA, while ROS production was visualized via DHE staining. Intracellular iron content was measured using an iron assay kit. Furthermore, the expression levels of p53, SLC7A11, and GPX4 were evaluated using Western blot. All experiments were performed in triplicate and independently repeated at least three times, and data were analyzed using Student’s t-test or one-way ANOVA, as appropriate. Results CPL significantly inhibited the proliferation and viability of 4T1 and MDA-MB-231 breast cancer cells in a dose-dependent manner, with IC50 values of 38.89 nM and 50.29 nM, respectively, and concomitantly suppressed cell migration and colony formation at higher concentrations. It also increased intracellular MDA and ROS and downregulated GSH, SLC7A11 and GPX4, inducing ferroptosis. siRNA knockdown of p53 attenuated CPL's effects, indicating p53's key role in CPL's anti-cancer activity. Conclusions This study provides evidence that CPL exerts anti-breast cancer effects by promoting ferroptosis through the p53/SLC7A11/GPX4 axis, highlighting its therapeutic potential as a novel agent for cancer treatment.

Freeze-casting polyamidoxime-based membrane adsorbents with synergistically enhanced mechanical properties and adsorption performance for uranium extraction from seawater - Yu He; Yanran Lu; Beibei Kang; Junxiang Wu; Xunshuang Zhang; Shilei Zhu; Zizhou Xu; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Journal of Environmental Chemical Engineering, 2026)

Roxithromycin disrupts nitrogen uptake and stress responses in wheat under nitrogen deficiency - Binbin Yu; Yier Yang; Keming Yang; Chunyu Jiang; Zefeng Yang; Yiru Zhao; Xiaoli Wang; Beibei Shen; Shaohu Ouyang; Zhongzhi Chen (Plant and Soil, 2026)

Sulfur dioxide maintains postharvest aroma quality of table grapes by modulating the lipoxygenase pathway and ethanol metabolism - Quanming Tian; Beibei Yin; Qing Shan; Yu Zhang; Jia Wei; Zheng Zhang; Yuyao Yuan; Bin Wu (Postharvest Biology and Technology, 2026)

Innovative application of a pH-sensitive indicator film: Monitoring the freshness of Larimichthys crocea based on the correlation model between hue value and TVB-N content - Yanfang Lv; Ziqi Yu; Ying Li; Beibei Ye; Jianrong Li; Xuepeng Li (Food Control, 2026)

Synergistically enhanced mechanical properties, wave-transparency, and low dielectric properties of cyanate ester resins by furfuryl-based diglycidyl-containing hollow polymer microspheres with nanoconfinement effects - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2026)

Sequential release of photodynamic hybrid HOFs and CeO₂ via a bilayer dynamic SIS hydrogel for periodontitis therapy - Shiqing Ma; Yujia Xiao; Yang Yu; Xiaotong Liu; Jiayin Deng; Yilin Yang; Shiyu Yao; Beibei Ma; Yo Shibata; Jun Zhou; Bo Zhao; Yuzhu Mu (Chemical Engineering Journal, 2026)

Modeling runoff with incomplete data: a comparison of hydrological, deep learning, and hybrid approaches - Jiarui Wu; Conrad Zorn; Weiru Zhao; Bjorn Klove; Wen Liu; Wenzhou Guo; Beibei Wang; Shengchao Qiao; Chaoqing Yu; Xiao Huang; Chao Wang (Journal of Hydrology, 2026)

Interface engineering of Si/graphene composites via compression-assisted fast joule heating for enhanced Lithium-ion battery anodes - Pengcheng Deng; Hang He; Tingting Yi; Junfeng Pan; Wenjie Liang; Beibei Yu; Zeman Xie; Zhijun Li; Danish Khan; Zeguo Tang; Xiao Yu; Dongjv Fu; et al. (Chemical Engineering Journal, 2026)

Resolving the damping-insulation-strength trilemma via dual-component yolk-shell architectures - Jiawei Du; Lu Zhang; Zhaohan Yu; Beibei Huang; Qikuan Cheng; Yunming Wang (Chemical Engineering Journal, 2026)

Protected areas as contested contact zones: Leopards, livestock, and the politics of coexistence - Duo Yin; Yiqing Wang; Beibei Liu; Yi Yu (Applied Geography, 2026)

Enhancing maize aboveground biomass estimation through time-series UAV-based multispectral and thermal imagery and improved FAO66 model - Guomin Shao; Wenting Han; Huihui Zhang; Beibei Zhou; Yi Wang; Yu Zhang; Li Yuan Zhang; Yaxiao Niu; Quan Xue (International Journal of Remote Sensing, 2026)

A scalable human liver-on-a-chip platform for predictive safety assessment - Gauri Kulkarni; Lizao Chen; Jing Sang; Ji Hye Seo; Romain Grall; Yunfang Wang; Paige Gilbride; Yu-Chieh Yuan; Matthew Albaum-Getzen; Jenna McCormack; Jingzhe Ma; Alyssa Fanelli; et al. (Toxicology, 2026)

Diversity loss of soil microbiome stimulates soil carbon emissions - Haibo Pan; Yingyi Fu; Hairong Tu; Yongxing Cui; Beibei Chen; Jiejun Qi; Ziheng Peng; Shi Chen; Chunling Liang; Jiai Liu; Xiaomeng Li; Min Gao; et al. (Soil Biology and Biochemistry, 2026)

Polyethylene microplastics specifically drive the dissemination of ARGs: Mechanisms involving microbial community restructuring and horizontal gene transfer - Xionghao Hu; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Zhaoyang Yan; Yang Li; Lei Zhang; Chao Wang; Xiaohui Lei; Bin Chen; et al. (Science of The Total Environment, 2026)

In situ-fabricated core-shell nanowire heterostructures for high-performance flexible thermoelectrics - Qikuan Cheng; Guangjun Luo; Zhaohan Yu; Yuxi Qi; Haotian Sun; Yi Yuan; Beibei Huang; Lu Zhang; Yunming Wang (Chemical Engineering Journal, 2026)

Low-temperature photothermal catalytic reforming: a promising approach for deep removal of biomass tar towards green fuels synthesis - Tianxiao Yu; Beibei Yan; Jian Li; Yuechi Che; Xiaopeng Jia; Guanyi Chen (Biomass and Bioenergy, 2026)

Enhanced removal of anionic Per- and polyfluoroalkyl substances (PFAS) by electrically assisted nanofiltration: Operational parameter optimization and mechanistic insights - YuTing Hua; Yu Li; Peng-Fei Li; BeiBei Chai; ZhiXuan Zhou; JingYi Wu (Journal of Hazardous Materials, 2026)

Comparative study by microwave, fixed-bed and rotary kiln pyrolysis of oily sludge: Petroleum hydrocarbons, N-/S-/Cl-containing pollutants and heavy metals - Jiantao Li; Hongdi Yu; Fawei Lin; Shupeng Zhang; Zizhen Niu; Zhihua Liu; Rui Zhang; Guijian Liu; Xiaojiang Shen; Beibei Yan; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

The global atmospheric model IGGatm based on Chinese reanalysis data and polynomial fitting formulas - Beibei Yu; Wei Li; Hongxing Zhang; Yunbin Yuan; Liu Hui (GPS Solutions, 2026)

Assessment of urban disaster resilience under the perspective of rainstorm waterlogging: A case study of the central urban area in Tianjin, China - Beibei Hu; Mengzhen Sun; Xingshuai Hou; Kunpeng Dong; Yue Chen; Yaxin Yu (Ocean & Coastal Management, 2026)

Investigation on chlorine migration during pyrolysis of medical waste - Tianxiao Yu; Tangwei Li; Jian Li; Muhammad Irfan Rajput; Beibei Yan; Guanyi Chen (Waste Management, 2026)

Modern pollen and stomatal assemblages in Northeastern China: Vegetation–climate relationships and paleoenvironmental implications - Jingfan He; Chunhai Li; Shi-Yong Yu; Xiaocen Li; Beibei Li (Review of Palaeobotany and Palynology, 2026)

The delay of Kyoho grape berry softening by SO₂ through the inhibition of cell wall polysaccharide structure and composition degradation - Quanming Tian; Shijun Xing; Beibei Yin; Yu Zhang; Zheng Zhang; Yuyao Yuan; Yage Xing; Jia Wei; Bin Wu (Postharvest Biology and Technology, 2026)

Identification and functional characterization of lycopene β-cyclase gene from Iris germanica and its relation to carotenoid accumulation - Xiaojie Zhao; Fang Yu; Xue Li; Yumeng Wu; Tianrui Gong; Beibei Su; Xiaofei Zhang; Dazhuang Huang (Journal of Plant Physiology, 2025)

Comparative hydrologic performance of cascading and distributed green-gray infrastructure: experimental evidence for spatial optimization in urban waterlogging mitigation - Jin You; Shuqian Wang; Minghu Ha; Aiqing Kang; Xiaohui Lei; Bin Chen; Yang Yu; Beibei Chai (Journal of Hydrology, 2025)

Photochemistry of acetylacetone: Droplets-mediated H2O2 generation and SO2 oxidation - Yu Lu; Lingdong Kong; Jiandong Shen; Beibei Liu; Yixuan An; Yuwen Wang; Jie Tan; Lin Wang (Atmospheric Environment, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Emergence and genomic characterization of Vibrio parahaemolyticus serotype O10:K4 from seafood-linked diarrheal cases in Zhejiang, China (2016–2023) - Jiewen Huang; Zhen Zhang; Qingtian Li; Jiancai Chen; Lingling Mei; Xiaojuan Qi; Lili Chen; Junyan Zhang; Chao Lv; Min Li; Honghu Chen; Yanjun Zhang; et al. (Food Research International, 2025)

The effect of photosensitization reaction of imidazole-2-carbaldehyde on the heterogeneous uptake of sulfur dioxide on hematite - Yixuan An; Lingdong Kong; Beibei Liu; Jiandong Shen; Yu Lu; Yuwen Wang; Jie Tan; Lin Wang (Atmospheric Environment, 2025)

Characteristics and influencing factors of ambient ozone pollution in Hangzhou in the relative humidity range with high ozone levels - Yu Lu; Lingdong Kong; Jiandong Shen; Beibei Liu; Yixuan An; Yuwen Wang; Jie Tan; Lin Wang (Atmospheric Pollution Research, 2025)

Enhanced storability of fresh walnut kernels with zein/tea polyphenol/apple pectin coatings by layer-by-layer assembly technique - Wenwen Li; Wenwen Zhang; Dengjie Yao; Muxi Yang; Beibei Zhang; Yu Qin; Delu Ning; Yongliang Zhuang; Lirong Li; Rui Huang (Food Control, 2025)

Aqueous photochemistry of brown carbon: H2O2 formation, enhanced SO2 oxidation, and the real role of excited triplets - Beibei Liu; Lingdong Kong; Yixuan An; Yu Lu; Yuwen Wang; Jie Tan; Xingfu Tang; Lin Wang (Atmospheric Environment, 2025)

Carbon dynamics, emission mitigation, and yield optimization in farmlands: A machine learning framework for multi-variable prediction - Beibei Wang; Xiao Huang; Hongxing He; Conrad Zorn; Jiangnan Wang; Wenzhou Guo; Jiarui Wu; Shengchao Qiao; Lingling Kong; Peifang Wang; Chaoqing Yu (Agricultural and Forest Meteorology, 2025)

Novel furfuryl-based phosphaphenanthrene containing N/P flame retardant: towards epoxy resin with excellent flame retardancy, enhanced toughness and low dielectric constant - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2025)

Full-scale studies are closer to reality than lab-scale ones: Tertiary treatment constructed wetlands maintain robust removal capability for pharmaceuticals and personal care products in cold weather conditions - Jiaxi Wang; Beibei Ye; Xia Yu; Ruiqi Yan; Hui Lin; Ying Man; Qian Sui (Bioresource Technology, 2025)

Three-dimensional experimental analysis of landslide-generated impulse waves in narrow reservoirs with variable local water depths - Chao Ke; Fasheng Miao; Yang Wang; Beibei Yang; Yiping Wu; Jizhixian Liu; Yu Zhang; Xi Li (Landslides, 2025)

Assessing the sustainability of water resources and analyzing influencing factors based on an improved ecological footprint model: a case study of Guangdong Province - Xin Xiang; Bo Li; Yu Yang; Menghua Li; Pan Wu; Pu Liu; Beibei Zhang; Ye Luo (Environment, Development and Sustainability, 2025)

Reclamation of available phosphorus and separation of heavy metals from sewage sludge via FeCl3-assisted electrokinetic treatment and pyrolysis - Xutong Wang; Huwei Li; Junxia Wang; Wolfram Buss; Anna Bogush; Ondřej Mašek; Youjun Zhang; Fan Yu; Beibei Yan; Zhanjun Cheng; Xiaoqiang Cui; Guanyi Chen; et al. (Journal of Environmental Management, 2025)

A review on the production of nutrient-enriched biochar: Insights from the evolution of nitrogen, phosphorus, and potassium - Xiaoqiang Cui; Xufeng Li; Junxia Wang; Xutong Wang; Fan Yu; Gaixiu Yang; Shiwei Xu; Zhanjun Cheng; Qianying Yang; Beibei Yan; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2025)

A novel role of PvUCP4 in Penaeus vannamei in response to Vibrio alginolyticus challenge - Zhengxinyu Liu; Caoyuan Han; FuHui Geng; XiaoTong Huang; BeiBei Dong; Yu Zhang; Weiguo Qian; Qingjian Liang (Fish & Shellfish Immunology, 2025)

Fusobacterium nucleatum-derived 3-indolepropionic acid promotes colorectal cancer progression via aryl hydrocarbon receptor activation in macrophages - Qi Song; Zhiliang Jin; Han Zhang; Kunqiao Hong; Beibei Zhu; Haisen Yin; Baoping Yu (Chemico-Biological Interactions, 2025)

Camellia nitidissima Chi extract ameliorates dextran sulfate sodium-induced acute ulcerative colitis in mice by inhibiting TLR4/NF-κB-mediated inflammatory activation - Lirong Li; Rui Huang; Wenwen Li; Dengjie Yao; Beibei Zhang; Mengna Li; Shunan Luo; Yu Qin; Wenwen Zhang (Inflammopharmacology, 2025)

Catalytic reforming of leachate from food waste towards hydrogen generation and wastewater treatment - Yongjie Hu; Yueyang Dai; Qi Gao; Yingying Yu; Yincheng Wang; Beibei Yan; Yanhui Men; Junyu Tao; Guanyi Chen (Journal of Water Process Engineering, 2025)

Effect of different zein/tea polyphenol/apple pectin coating on nutritional, physicochemical properties of fresh walnut kernel preservation - Wenwen Li; Yu Qin; Beibei Zhang; Wenwen Zhang; Dengjie Yao; Chunyin Zeng; Delu Ning; Yongliang Zhuang; Lirong Li; Rui Huang (Food Chemistry, 2025)

Network pharmacological analysis and experimental verification of Zisheng Tongmai decoction in the treatment of premature ovarian failure - Jiaru Wu; Mengjie Wen; Zecheng Wang; Kun Yu; Xinyue Jin; Chenxu Liu; Qiuhang Song; Guohong Zhang; Beibei Wu; Yunfeng Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Transformation, bound-residue formation, translocation of tribromobisphenol A, 2,2′-dibromobisphenol A, 2,6-bromobisphenol A, and monobromobisphenol A in submerged soil and soil-rice seedling systems - Yunjiang Yu; Chang Zhou; Beibei Li; Shiming Zhai; Jie Zhong; Hang Wei; Zhiliang Chen; Mingdeng Xiang; Guocheng Hu; Bingbing Sun (Journal of Environmental Management, 2025)

Vinylene-linked covalent organic frameworks based on phenanthroline for visible-light-driven bifunctional photocatalytic water splitting - Haonan Sun; Haifeng Ji; Danyang Qiao; Yang Xu; Xiongwei Qu; Yu Qi; Zhaochi Feng; Xiaojie Zhang; Fuxiang Zhang; Ruihu Wang; Beibei Dong (Chemical Engineering Journal, 2025)

Comprehensive evaluation of groundwater quality in population-dense and extensive agricultural regions and study on its relationship with agricultural production and human activities - Beibei Zhang; Xin Hu; Yu Yang; Xiangzhao Deng; Bo Li; Xiaoyu Gong; Xin Xiang; Xutao Cai; Tongqing Liu (Environmental Geochemistry and Health, 2025)

How to stop groundwater drawdown in North China Plain? Combining agricultural management strategies and climate change - Junji Ou; Beibei Ding; Puyu Feng; Yong Chen; Lili Yu; De Li Liu; Raghavan Srinivasan; Xueliang Zhang (Journal of Hydrology, 2025)

Temporal and spatial changes of glacial lakes in the central Himalayas and their response to climate change based on multi-source remote sensing data - Xiaoqiang Cheng; Donghui Shangguan; Chengsheng Yang; Wangping Li; Zhaoye Zhou; Xiaojie Liu; Da Li; Xiuxia Zhang; Huilan Ding; Zewei Liu; Yi Yu; Xiaoxian Wang; et al. (Global and Planetary Change, 2025)

Synergistic catalysis of dual-sites promoted cycloaddition of CO2 with epoxides - Shiling Zhao; Kaizhi Wang; Beibei Yang; Zehui Sun; Yu Zhao (Fuel, 2025)

Analysis of lead contamination sources in roadside soil via the isotope tracing method - Aihua Yu; Qiyue Yang; Beibei Xu; Yu Yang; Zhijian Ren; Kangjian Li (Journal of Environmental Chemical Engineering, 2024)

Peroxymonosulfate Activation by MnO2/CoMoO4/NF for Degradation of Levofloxacin - Yonglei Xing; Huijuan Liu; Yu Ha; Xiaoyong Jin; Beibei Kou; Rui Yang; Gang Ni (Water, Air, & Soil Pollution, 2024)

Transcriptome analysis of hepatopancreas revealed the role of autophagy under nitrite stress in Pacific white shrimp (Penaeus vannamei) - Xinghao Lin; Zhengxinyu Liu; Jiaqian Chen; Xiaotong Huang; Wanghao Du; Yu Zhang; Beibei Dong; Qingjian Liang (Aquaculture International, 2024)

Efficient reclamation of phosphorus from wetland biomass waste via liquid-recirculated hydrothermal carbonization and precipitation - Junxia Wang; Yuting Wang; Fan Yu; Jiangtao Wang; Xutong Wang; Jipeng Luo; Chao He; Xiaoqiang Cui; Beibei Yan; Guanyi Chen (Water Research, 2024)

Bridging ecological processes to diversity formation and functional profiles in belowground bacterial communities - Beibei Chen; Ziheng Peng; Shi Chen; Yu Liu; Jiejun Qi; Haibo Pan; Hang Gao; Jiamin Gao; Chunling Liang; Jiai Liu; Xun Qian; Xiao Zhang; et al. (Soil Biology and Biochemistry, 2024)

Additive patterns in near-infrared diffuse reflectance spectra: Implications for product formulation and analysis - Le Zhao; Youyan Liang; Nuohan Zhang; Yanbin Chang; Meijuan Fan; Cong Wang; Beibei Li; Hongbo Wang; Yu Liu; Hongxiao Yu; Song Yang; Fuwei Xie; et al. (Food Control, 2024)

Selective hydrogenation of biphenyl to cyclohexylbenzene over Cu based catalysts - Shiling Zhao; Kaizhi Wang; Beibei Yang; Yu Zhao; Jingxuan Cai (Chemical Engineering Journal, 2024)

Green transformation of oily sludge through geopolymer: Material properties and hydration mechanisms - Xuan Guo; Hongdi Yu; Hongyun Yao; Fawei Lin; Eslam Salama; Mona Ossman; Beibei Yan; Guanyi Chen (Chemosphere, 2024)

Pollutant degradation and hydrogen production of landfill leachate membrane concentrates via aqueous phase reforming - Yingying Yu; Yincheng Wang; Chen Chen; Qingguo Bu; Junyu Tao; Xiaopeng Jia; Junhao Sun; Beibei Yan; Guanyi Chen (Chemosphere, 2024)

Quantifying the negative effects of dissolved organic carbon of maize straw-derived biochar on its carbon sequestration potential in a paddy soil - Lanfang Han; Beibei Liu; Yu Luo; Liying Chen; Chuanxin Ma; Chao Xu; Ke Sun; Baoshan Xing (Soil Biology and Biochemistry, 2024)

Microplastics increase the microbial functional potential of greenhouse gas emissions and water pollution in a freshwater lake: A metagenomic study - Tianyu Zhuo; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Yang Li; Yuan Meng; Lifeng Wu; Bin Chen (Environmental Research, 2024)

A “MOF-plus-MOF” strategy to synthesize Co-N3C1 single-atom catalyst for rechargeable Zn-air battery - Chenhao Lv; Beibei Li; Yangyang Ren; Guichao Zhang; Zunming Lu; Lanlan Li; Xinghua Zhang; Xiaojing Yang; Xiaofei Yu (Chemical Engineering Journal, 2024)

Linking regional species pool size to dispersal–selection relationships in soil fungal communities across terrestrial ecosystems - Beibei Chen; Haibo Pan; Xiaofeng Song; Yajun Yao; Jiejun Qi; Xiaoli Bai; Ziheng Peng; Yu Liu; Shi Chen; Hang Gao; Chunling Liang; Jiai Liu; et al. (Global Ecology and Biogeography, 2024)
Aim Revealing the role of regional species pool size in community assembly rules is essential for extending the species‐pool framework to large‐scale community ecology, and thus for more comprehensive understanding of biodiversity formation. However, little has been done to couple the regional species‐pool effect into local ecological processes in soil fungal communities, which play essential roles in ecosystems worldwide. Here, we performed large‐scale soil surveys of fungal communities to examine the linkage between regional species pool size and D ispersal– S election R elationships (DSRs), and their relations to community structure. Location China. Time period July–August 2019. Major taxa studied Fungal communities. Methods By conducting the nationwide soil survey of ~1200 samples from various ecosystems across China, including agricultural, forest, grassland, and wetland soils, we examined the linkage between regional species pool size and DSRs, and their relationship to fungal community structure. Results We found that selection was negatively related to dispersal, which was consistent with the general view that the strength of selection is weakened by dispersal homogenization, and that this relationship was stronger in regions with larger species pools. Moreover, an increase in community dispersion was correlated with stronger effect size of DSRs, implying greater heterogeneity among fungal communities under larger species pools. Main conclusions Our study clearly illustrates the association of regional species pool size with local assembly rules and community formation of soil fungi across terrestrial ecosystems.

Rapid Joule heating-induced welding of silicon and graphene for enhanced lithium-ion battery anodes - Fan Yang; Pengcheng Deng; Hang He; Ruolan Hong; Kun Xiang; Yuan Cao; Beibei Yu; Zeman Xie; Jiming Lu; Zikang Liu; Danish Khan; David Harbottle; et al. (Chemical Engineering Journal, 2024)

Priming effects of surface soil organic carbon decreased with warming: a global meta-analysis - Hongxin Dong; Junjie Lin; Jiayu Lu; Lujun Li; Zhiguo Yu; Amit Kumar; Qin Zhang; Dan Liu; Beibei Chen (Plant and Soil, 2024)

Hydrochemical analysis and quality comprehensive assessment of groundwater in the densely populated coastal industrial city - Xin Hu; Bo Li; Beibei Zhang; Yu Yang; Xutao Cai; Xiaoyu Gong; Xin Xiang; Tingliang Wu (Journal of Water Process Engineering, 2024)

Direct aqueous photochemistry of methylglyoxal and its effect on sulfate formation - Jie Tan; Lingdong Kong; Yuwen Wang; Beibei Liu; Yixuan An; Lianghai Xia; Yu Lu; Qing Li; Lin Wang (Science of The Total Environment, 2024)

Experimental investigation on the effect of vent film material and thickness and hydrogen fraction on explosion-venting features of H2/CO/Air mixtures within a horizontal duct - Beibei Qi; Haitao Li; Minggao Yu; Chengcai Wei; Jingyu Cui; Fuer Zhai (Process Safety and Environmental Protection, 2024)

Transcription and splicing variations of SR genes accompany with genome-wide accumulation of long-introns in pine - Shanlan Chen; Yingjie Zhang; Li Liu; Yujian Mo; Junyi Li; Beibei Chen; Yi Zhou; Jinxing Lin; Xingyu Jiang; Long Wei; Yu Ling (Plant Science, 2024)

Absorption and translocation of selected pharmaceuticals in Pistia stratiotes: Spatial distribution analysis using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry - Jiaxi Wang; Yiwen Zhu; Beibei Ye; Junling Dun; Xia Yu; Qian Sui (Journal of Hazardous Materials, 2024)

Co-pyrolysis of saw dust and oily sludge with waste-heat utilization of steel slag on rotary kiln simulated engineering practice - Hongdi Yu; Fawei Lin; Xuan Guo; Hongyun Yao; Fa Zheng; Jiantao Li; Meng Zhang; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2024)

Spatiotemporal patterns and driving factors of gross primary productivity over the Mongolian Plateau steppe in the past 20 years - Lei Ding; Zhenwang Li; Xu Wang; Beibei Shen; Liujun Xiao; Gang Dong; Lu Yu; Banzragch Nandintsetseg; Zhou Shi; Jinfeng Chang; Changliang Shao (Science of The Total Environment, 2024)

State-of-the-art conceptual design of supercritical carbon dioxide as a green technology involved in bioresource conversion processes - Beibei Yan; Yongjie Hu; Jian Wang; Junyu Tao; Shaige Xia; Wenzhe Yang; Yu Zhang; Guo Chen; Wendi Zhou; Guanyi Chen (Chemical Engineering Journal, 2024)

Protective effects of l-cysteine and N-acetyl-l-cysteine on boar sperm quality during hypothermic liquid storage with bovine serum albumin as a protectant - Diqi Yang; Xiaomei Yu; Xiaoping Li; Beibei Yu; Hui Peng (Theriogenology, 2024)

Nitrogen removal performance and mechanisms of three aquatic plants for farmland tail water purification - Si-Yi Zhang; Xuejian Liu; Beibei Hao; Ying Liang; Yu Ma; Nan Wang; Zhihua Zhang; Bin He (Science of The Total Environment, 2024)

A sensitive bimetallic copper/bismuth metal-organic frameworks-based aptasensors for zearalenone detection in foodstuffs - Mengmeng Kang; Yu Yao; Beibei Yuan; Shuai Zhang; Olayinka Oderinde; Zhihong Zhang (Food Chemistry, 2024)

Reaction pathway of hydrothermal liquefaction of duckweed for wastewater treatment based on major model compounds - Yingying Yu; Kaige Zhao; Wanqing Li; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Junyu Tao; Xiaopeng Jia; Junhao Sun (Biomass and Bioenergy, 2024)

Perfluoroalkyl acid precursors in agricultural soil-plant systems: Occurrence, uptake, and biotransformation - Beibei Ye; Jiaxi Wang; Lei Zhou; Xia Yu; Qian Sui (Science of The Total Environment, 2024)

Experimental and reaction kinetics studies on deflagration characteristics of liquefied petroleum gas-air mixture with different compositions in confined space - Chengcai Wei; Haitao Li; Zhenmin Luo; Yingying Yu; Minggao Yu; Kai Zheng; Bin Su; Beibei Qi; Fengchuan Wang (Fuel, 2024)

The mechanism of photothermal catalytic reforming of biomass tar: An exploratory study based on density functional theory - Beibei Yan; Tianxiao Yu; Jian Li; Xiaopeng Jia; Zhiyu Li; Yuechi Che; Guanyi Chen; Juan Zhao (Fuel, 2024)

Coupling electrokinetic technique with hydrothermal carbonization for phosphorus-enriched hydrochar production and heavy metal separation from sewage sludge - Xutong Wang; Ondřej Mašek; Huwei Li; Fan Yu; Christian Wurzer; Junxia Wang; Beibei Yan; Xiaoqiang Cui; Guanyi Chen; Li'an Hou (Chemical Engineering Journal, 2024)

Effect of heterogeneous fenton-like pretreatment on semi-permeable membrane-covered co-composting: Humification and microbial community succession - Yingjin Song; Yu Hou; Lan Mu; Guanyi Chen; Yamei Zeng; Beibei Yan (Bioresource Technology, 2024)

BDE-47 induces metabolic dysfunction-associated steatotic liver disease (MASLD) through CD36-mediated increased fatty acid uptake and PPARα-induced abnormal fatty acid oxidation in BALB/c mice - Beibei Xia; Rongfei Yu; Junxiong Liu; Dongmeng Liu; Shasha Li; Liu Yang; Nan Liu; Bosen Liang; Jiajing Zeng; Jinhua Wei; Guimiao Lin (Toxicology Letters, 2024)

Nitrogen source affects non-aeration microalgal-bacterial biofilm growth progression and metabolic function during greywater treatment - Jiake Li; Beibei Wu; Meng Xu; Xuan Han; Yinuo Xing; Yu Zhou; Mengyao Ran; Yun Zhou (Bioresource Technology, 2024)

The neglected roles of adjacent natural ecosystems in maintaining bacterial diversity in agroecosystems - Ziheng Peng; Yunfeng Yang; Yu Liu; Lianyan Bu; Jiejun Qi; Hang Gao; Shi Chen; Haibo Pan; Beibei Chen; Chunling Liang; Xiaomeng Li; Yining An; et al. (Global Change Biology, 2024)
A central aim of community ecology is to understand how local species diversity is shaped. Agricultural activities are reshaping and filtering soil biodiversity and communities; however, ecological processes that structure agricultural communities have often overlooked the role of the regional species pool, mainly owing to the lack of large datasets across several regions. Here, we conducted a soil survey of 941 plots of agricultural and adjacent natural ecosystems (e.g., forest, wetland, grassland, and desert) in 38 regions across diverse climatic and soil gradients to evaluate whether the regional species pool of soil microbes from adjacent natural ecosystems is important in shaping agricultural soil microbial diversity and completeness. Using a framework of multiscales community assembly, we revealed that the regional species pool was an important predictor of agricultural bacterial diversity and explained a unique variation that cannot be predicted by historical legacy, large‐scale environmental factors, and local community assembly processes. Moreover, the species pool effects were associated with microbial dormancy potential, where taxa with higher dormancy potential exhibited stronger species pool effects. Bacterial diversity in regions with higher agricultural intensity was more influenced by species pool effects than that in regions with low intensity, indicating that the maintenance of agricultural biodiversity in high‐intensity regions strongly depends on species present in the surrounding landscape. Models for community completeness indicated the positive effect of regional species pool, further implying the community unsaturation and increased potential in bacterial diversity of agricultural ecosystems. Overall, our study reveals the indubitable role of regional species pool from adjacent natural ecosystems in predicting bacterial diversity, which has useful implication for biodiversity management and conservation in agricultural systems.

Effects of nitrification and urease inhibitors on ammonia-oxidizing microorganisms, denitrifying bacteria, and greenhouse gas emissions in greenhouse vegetable fields - Luzhen Li; Changsheng Zhao; Xinghua Wang; Yu Tan; Xiaokai Wang; Xuzhen Liu; Beibei Guo (Environmental Research, 2023)

Constructing MoS2-SnS heterostructures on N-doped carbon nanosheets for enhanced catalytic conversion of polysulfides in lithium-sulfur batteries - Junpu Zhang; Wen Xi; Feng Yu; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Chemical Engineering Journal, 2023)

Intrinsic mechanism for the removal of antibiotic pollution by a dual coagulation process from the perspective of the interaction between NOM and antibiotic - Kangying Guo; Chenghui Yu; Baoyu Gao; Beibei Liu; Zhining Wang; Yan Wang; Qinyan Yue; Yue Gao (Water Research, 2023)

A review of treatment technologies for acid mine drainage and sustainability assessment - Yu Yang; Bo Li; Tao Li; Pu Liu; Beibei Zhang; Lulu Che (Journal of Water Process Engineering, 2023)

Outdoor environmental exposome and the burden of tuberculosis: Findings from nearly two million adults in northwestern China - Jia-Xin Li; Qiyun Luan; Beibei Li; Shyamali C. Dharmage; Joachim Heinrich; Michael S. Bloom; Luke D. Knibbs; Igor Popovic; Li Li; Xuemei Zhong; Aimin Xu; Chuanjiang He; et al. (Journal of Hazardous Materials, 2023)

Combined virome analysis and metagenomic sequencing to reveal the viral communities and risk of virus–associated antibiotic resistance genes during composting - Zhengfu Yue; Jing Zhang; Jing Zhang; Xingxiang Wang; Lirong Li; Haiyang Yu; Beibei Liu; Qinfen Li; Dong Zhu; Yukun Zou (Journal of Hazardous Materials, 2023)

La0.7(Ca, Sr)0.3Ni0.6Mn0.5O3 perovskites for photothermal catalytic reforming of toluene: The role of oxygen species in the photothermal synergistic effect - Xiaoshan Dong; Jian Wang; Fawei Lin; Jian Li; Tianxiao Yu; Beibei Yan; Guanyi Chen (Fuel, 2023)

Correction to: Exploration of the potential common pathogenic mechanisms in COVID‑19 and silicosis by using bioinformatics and system biology - Yunze Tian; Beibei Yu; Yongfeng Zhang; Sanpeng Zhang; Boqiang lv; Shouping Gong; Jianzhong Li (Functional & Integrative Genomics, 2023)

Exploration of the potential common pathogenic mechanisms in COVID-19 and silicosis by using bioinformatics and system biology - Yunze Tian; Beibei Yu; Yongfeng Zhang; Sanpeng Zhang; Boqiang lv; Shouping Gong; Jianzhong Li (Functional & Integrative Genomics, 2023)
Silicosis is an occupational lung disease that is common worldwide. In recent years, coronavirus disease 2019 (COVID-19) has provided daunting challenges to public healthcare systems globally. Although multiple studies have shown a close link between COVID-19 and other respiratory diseases, the inter-relational mechanisms between COVID-19 and silicosis remain unclear. This study aimed to explore the shared molecular mechanisms and drug targets of COVID-19 and silicosis. Gene expression profiling identified four modules that were most closely associated with both diseases. Furthermore, we performed functional analysis and constructed a protein–protein interaction network. Seven hub genes (budding uninhibited by benzimidazoles 1 [BUB1], protein regulator of cytokinesis 1 [PRC1], kinesin family member C1 [KIFC1], ribonucleotide reductase regulatory subunit M2 [RRM2], cyclin-dependent kinase inhibitor 3 [CDKN3], Cyclin B2 [CCNB2], and minichromosome maintenance complex component 6 [MCM6]) were involved in the interaction between COVID-19 and silicosis. We investigated how diverse microRNAs and transcription factors regulate these seven genes. Subsequently, the correlation between the hub genes and infiltrating immune cells was explored. Further in-depth analyses were performed based on single-cell transcriptomic data from COVID-19, and the expression of hub-shared genes was characterized and located in multiple cell clusters. Finally, molecular docking results reveal small molecular compounds that may improve COVID-19 and silicosis. The current study reveals the common pathogenesis of COVID-19 and silicosis, which may provide a novel reference for further research.

Hydrostatic pressure drives microbe-mediated biodegradation of microplastics in surface sediments of deep reservoirs: Novel findings from hydrostatic pressure simulation experiments - Kehong Yu; Beibei Chai; Tianyu Zhuo; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Bin Chen (Water Research, 2023)

c-Jun N-terminal kinase activation contributes to improving low temperature tolerance via regulating apoptosis in the Pacific white shrimp Penaeus vannamei - JieRen Zheng; Ying Zhao; YuXin Feng; WeiGuo Qian; Yu Zhang; BeiBei Dong; QingJian Liang (Fish & Shellfish Immunology, 2023)

Enhancing wuyiencin productivity of Streptomyces albulus (CK15) by mutagenesis breeding with atmospheric and room temperature plasma - Yu Wah Thein; Liming Shi; Binghua Liu; Qiuhe Wei; Kecheng Zhang; Beibei Ge (World Journal of Microbiology and Biotechnology, 2023)

Pyrolysis/combustion potential and heavy metal risk of oily sludge and derived products in industrial scale - Hongdi Yu; Jiantao Li; Fawei Lin; Menglan Zeng; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

The efficiency of full-scale subsurface constructed wetlands with high hydraulic loading rates in removing pharmaceutical and personal care products from secondary effluent - Jiaxi Wang; Xia Yu; Hui Lin; Jiusi Wang; Liping Chen; Yanzhou Ding; Shuai Feng; Jingjing Zhang; Beibei Ye; Xiping Kan; Qian Sui (Journal of Hazardous Materials, 2023)

Proliferation toxicity and mechanism of novel mixed bromine/chlorine transformation products of tetrabromobisphenol A on human embryonic stem cell - Yan Yang; Shiyao He; Zenghua Qi; Xuyang Chai; Qiting Zhao; Beibei Hu; Guiying Li; Yingxin Yu (Journal of Hazardous Materials, 2023)

The recycling potential of unregulated waste electrical and electronic equipment in China: Generation, economic value, and cost-benefit analysis - Bingbing Sun; Beibei Li; Shexia Ma; Ming Zhu; Chenyin Dong; Mingdeng Xiang; Hefa Cheng; Yunjiang Yu (Journal of Cleaner Production, 2023)

Phosphate-solubilizing microorganisms regulate the release and transformation of phosphorus in biochar-based slow-release fertilizer - Zhongwang Liu; Zhansheng Wu; Fei Tian; Xiaochen Liu; Tao Li; Yanhui He; Beibei Li; Ziyan Zhang; Bing Yu (Science of The Total Environment, 2023)

scRNA-seq analysis reveals toxicity mechanisms in shrimp hemocytes subjected to nitrite stress - QingJian Liang; BeiBei Dong; Ang Li; LiTing Wu; Yu Zhang; Tao Han; Xing Liu (Chemosphere, 2023)

Knockdown of Csnk1a1 results in preimplantation developmental arrest in mice - Zengyou Ma; Haoyi Zheng; Xiaoping Li; Beibei Yu; Hui Peng (Theriogenology, 2023)

Long-term non-phosphorus application increased paddy methane emission by promoting organic acid and methanogen abundance in Tai Lake region, China - Chen Xu; Susu Shen; Beibei Zhou; Yuanyuan Feng; Zhu He; Linlin Shi; Yu Wang; Haihou Wang; Tripti Mishra; Lihong Xue (Science of The Total Environment, 2023)

Comprehensive understanding of guest compound intercalated layered double hydroxides: Design and applications in removal of potentially toxic elements - Shihao Cui; Yutao Peng; Xiao Yang; Xing Gao; Chung-Yu Guan; Beibei Fan; Xue Zhou; Qing Chen (Critical Reviews in Environmental Science and Technology, 2023)

Mixed bromine/chlorine transformation products of tetrabromobisphenol A formed in the combustion of printed circuit boards: Emission characteristics and transformation pathways - Xiang Ge; Yanpeng Gao; Yan Yang; Guanhui Chen; Shengtao Ma; Beibei Hu; Yingxin Yu; Taicheng An (Science of The Total Environment, 2023)

Estimation of the soil arsenic concentration using a geographically weighted XGBoost model based on hyperspectral data - Miao Ye; Lin Zhu; Xiaojuan Li; Yinghai Ke; Yong Huang; Beibei Chen; Huilin Yu; Huan Li; Hui Feng (Science of The Total Environment, 2023)

Influence of uncoordinated N content on Ni N C electrocatalyst for CO2 reduction: Combining first principle with machine learning - Beibei An; Guanyao Yu; Jinya Li; Yuanyuan Li; Li Wang; Jinglai Zhang (Fuel, 2023)

Aeration-free greywater treatment in a self-sustaining oxygenic photobiofilm: Performance and mechanisms - Wenxiao Yin; Zixuan Yu; Mengxi Gao; Qianyi Liu; Beibei Wu; Tian Ren; Yun Zhou (Chemical Engineering Journal, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Design and Experimental Study of Core Bit for Hard Rock Drilling in Deep-Sea - Xingchen Li; Liang Xiong; Wenwei Xie; Ke Gao; Yutao Shao; Yunlong Chen; Yanjiang Yu; Beibei Kou; Qiuping Lu; Jing Zeng; Haoyu Yu (Journal of Marine Science and Engineering, 2023)
The hard rock stratum will seriously affect the efficiency of deep-sea drilling and greatly increase the cost of drilling operations due to its complexity. In ocean drilling operations, the design of the bit is critical. Therefore, the core bit should be able to drill in a variety of formations, especially in hard rock stratum, with the function of reducing the need to change the bit due to formation changes and improving the drilling efficiency. In this paper, three different core bits were designed according to the hard rock stratum of the seabed: the roller bit, diamond bit and bionic bit. According to the test results, it was observed that: (1) It is fully proven that the roller core bit has the characteristics of stable drilling in hard strata, small torque and high drilling efficiency. The same method can realize the core in shallow soft strata through the setting of drilling parameters. (2) For the diamond bit, the field test data show that the new formula diamond bit has a good adaptability to the changing hard rock strata in this area, with an average rate of penetration (ROP) of 4.4 m/h and a bit life of 137.75 m. (3) For the bionic bit, field experiment data showed that drilling in the formation lithology was gray green tuff, which had a core recovery up to 100%. The average ROP was 1.35 m/h, and the highest ROP was 1.88 m/h. The design and experiment of three kinds of drill bits have effectively solved the technical problem of efficient drilling in deep-sea hard-rock stratum.

Waste to treasure: Superwetting foam enhanced by bamboo powder for sustainable on-demand oil-water separation - Dong Wu; Shunyou Hu; Beibei Lu; Yuanyuan Hu; Mi Wang; Wen Yu; Gui-Gen Wang; Jiaheng Zhang (Journal of Hazardous Materials, 2023)

Soluble and colorless polyimide coated cotton fabric with attractive multifunction: Warmth retention, breathable, antifouling, UV and acid resistance - Dengpeng Song; Beibei Jiang; Jiayan Zhou; Yiwei Ouyang; Yu Zhang; Chong Gao; Kunkun Zhu; Yang Liu; Weilin Xu (Chemical Engineering Journal, 2023)

Co-composting of cattle manure and wheat straw covered with a semipermeable membrane: organic matter humification and bacterial community succession - Yingjin Song; Ruiyi Li; Yuxin Wang; Yu Hou; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Lan Mu (Environmental Science and Pollution Research, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Low-Level Environmental Per- and Polyfluoroalkyl Substances and Preterm Birth: A Nested Case–Control Study Among a Uyghur Population in Northwestern China - Bo-Yi Yang; Jianhua Wu; Xilong Niu; Chuanjiang He; Michael S. Bloom; Maihefuzaimu Abudoukade; Mairiyemu Abulizi; Aimin Xu; Beibei Li; Li Li; Xuemei Zhong; Qi-Zhen Wu; et al. (Exposure and Health, 2022)

Core phylotypes enhance the resistance of soil microbiome to environmental changes to maintain multifunctionality in agricultural ecosystems - Shuo Jiao; Jiejun Qi; Chujie Jin; Yu Liu; Yang Wang; Haibo Pan; Shi Chen; Chunling Liang; Ziheng Peng; Beibei Chen; Xun Qian; Gehong Wei (Global Change Biology, 2022)
Agricultural ecosystems are facing increasing environmental changes. Revealing ecological stability of belowground organisms is key to developing management strategies that maintain agricultural ecosystem services in a changing world. Here, we collected soils from adjacent pairs of maize and rice fields along large spatial scale across Eastern and Southeast China to investigate the importance of core microbiota as a predictor of resistance of soil microbiome (e.g. bacteria, fungi and protist) to climate changes and nutrient fertilization, and their effect on multiple ecosystem functions, representing key services for crop growth and health in agro‐ecosystems. Soil microbiome in maize soils exhibited stronger resistance than that in rice soils, by considering multiple aspects of the resistance index, for example, community, phylogenetic conservation and network complexity. Community resistance of soil microbiome showed a geographic pattern, with higher resistance at lower latitudes, suggesting their stronger resistance in warmer regions. Particularly, we highlighted the role of core phylotypes in enhancing the community resistance of soil microbiome, which was essential for the maintenance of multifunctionality in agricultural ecosystems. Our results represent a significant advance in linking core phylotypes to community resistance and ecosystem functions, and therefore forecasting agro‐ecosystems dynamics in response to ongoing environmental changes. These suggest that core phylotypes should be considered a key factor in enhancing agricultural sustainability and crop productivity under global change scenarios.

Screening and production of dsRNA molecules for protecting Cucumis sativus against Cucumber mosaic virus through foliar application - Qin Mo; Beibei Lv; Yu Sun; Xiao Wu; Lili Song; Run Cai; Xueming Tang (Plant Biotechnology Reports, 2022)

Coupling effect of annular volume change and non-linear fluid thermal property on annular pressure buildup in multi-layer annuluses of deepwater well - Jing Zeng; BeiBei Kou; Huaqing Liu; Yanjiang Yu; Jing Li; Bin Li; Xingchen Li; Dejun Cai (Arabian Journal of Geosciences, 2022)

A multi-dosing regimen to enhance the spatial memory of normal rats with α5-containing GABAA receptor negative allosteric modulator L-655,708 - Congcong Yuan; An Gao; Qiang Xu; Beibei Zhang; Rui Xue; Yan Dou; Chunshui Yu (Psychopharmacology, 2021)

Alantolactone exhibits antiproliferative and apoptosis-promoting properties in colon cancer model via activation of the MAPK-JNK/c-Jun signaling pathway - Yijing Ren; Cheng Lv; Jing Zhang; Beibei Zhang; Bei Yue; Xiaoping Luo; Zhilun Yu; Hao Wang; Junyu Ren; Zhengtao Wang; Wei Dou (Molecular and Cellular Biochemistry, 2021)

Adsorption performance and mechanisms of mercaptans removal from gasoline oil using core-shell AC-based adsorbents - Pamphile Ndagijimana; Xuejiao Liu; Zhiwei Li; Zhenjiao Xing; Beibei Pan; Guangwei Yu; Yin Wang (Environmental Science and Pollution Research, 2021)

Spatio-temporal analysis of cropland change in the Guanzhong area, China, from 1650 to 2016 - Xueqiong Wei; Yuanfang Li; Yu Guo; Tiexi Chen; Beibei Li (Journal of Geographical Sciences, 2021)

Hydrogen alleviates cell damage and acute lung injury in sepsis via PINK1/Parkin-mediated mitophagy - Hongguang Chen; Huaying Lin; Beibei Dong; Yaoqi Wang; Yonghao Yu; Keliang Xie (Inflammation Research, 2021)

Metabolic characteristics and nutrient utilization in high-feed-efficiency pigs selected using different feed conversion ratio models - Beibei He; Tiantian Li; Wei Wang; Hang Gao; Yu Bai; Shuai Zhang; Jianjun Zang; Defa Li; Junjun Wang (Science China Life Sciences, 2019)

Evolution model of a modern delta fed by a seasonal river in Daihai Lake, North China: determined from ground-penetrating radar and trenches - Beibei Liu; Chengpeng Tan; Xinghe Yu; Xin Shan; Shunli Li (Frontiers of Earth Science, 2019)

Responses of primary producers in shallow lakes to elevated temperature: a mesocosm experiment during the growing season of Potamogeton crispus - Beibei Hao; Anna Fabrin Roejkjaer; Haoping Wu; Yu Cao; Erik Jeppesen; Wei Li (Aquatic Sciences, 2018)

Comparison of genetic diversity in four Typha species (Poales, Typhaceae) from China - Beibei Zhou; Dan Yu; Zhenjie Ding; Xinwei Xu (Hydrobiologia, 2016)

Nitrous Oxide Production in River Sediment of Highly Urbanized Area and the Effects of Water Quality - Dongqi Wang; Yongjie Tan; Zhongjie Yu; Yangjie Li; Siqi Chang; Huanguang Deng; Beibei Hu; Zhenlou Chen (Wetlands, 2015)

Identification of polycyclic aromatic hydrocarbons in soils in Taizhou, East China - Guanjiu Hu; Sulan Chen; Wei Shi; Beibei Zhang; Yong Zhang; Juan Huang; Jun Chen; John P. Giesy; Hongxia Yu (Environmental Geochemistry and Health, 2015)

Maged1 Co-interacting with CREB Through a Hexapeptide Repeat Domain Regulates Learning and Memory in Mice - JianJun Yang; BeiBei Lai; AiLi Xu; Yu Liu; XiaoMin Li; YongNa Zhao; WeiFeng Li; MuHuo Ji; Gang Hu; Xiang Gao; Jun Gao (Molecular Neurobiology, 2015)

Carbon emissions induced by cropland expansion in Northeast China during the past 300 years - BeiBei Li; XiuQi Fang; Yu Ye; XueZhen Zhang (Science China Earth Sciences, 2014)

Population genetic diversity and divergence of the halobiotic herb Limonium sinense estimated by AFLP and ISSR, and implications for conservation - Ge Ding; Daizhen Zhang; Yanqiu Yu; Lingling Zhao; Beibei Zhang (Plant Systematics and Evolution, 2013)

Putative type VI secretion systems of Vibrio parahaemolyticus contribute to adhesion to cultured cell monolayers - Ying Yu; Hong Yang; Jun Li; Peipei Zhang; Beibei Wu; Binglin Zhu; Yan Zhang; Weihuan Fang (Archives of Microbiology, 2012)

Accuracy assessment of global historical cropland datasets based on regional reconstructed historical data—A case study in Northeast China - BeiBei Li; XiuQi Fang; Yu Ye; XueZhen Zhang (Science China Earth Sciences, 2010)

Characterization and expression profiling of tyrosine aminotransferase gene from Salvia miltiorrhiza (Dan-shen) in rosmarinic acid biosynthesis pathway - Beibei Huang; Bo Yi; Yanbing Duan; Lianna Sun; Xiaojing Yu; Jing Guo; Wansheng Chen (Molecular Biology Reports, 2008)

Heterologous production of secondary metabolites as pharmaceuticals in Saccharomyces cerevisiae - Beibei Huang; Jing Guo; Bo Yi; Xiaojing Yu; Lianna Sun; Wansheng Chen (Biotechnology Letters, 2008)

A genome-wide comparison of genes responsive to autopolyploidy inIsatis indigotica usingArabidopsis thaliana Affymetrix genechips - Beibei Lu; Xinzhu Pan; Lei Zhang; Beibei Huang; Lianna Sun; Bin Li; Bo Yi; Shuiqing Zheng; Xiaojing Yu; Ruxian Ding; Wansheng Chen (Plant Molecular Biology Reporter, 2006)